Self-rated health among older adults in two fast ageing European countries: evidence from Italy and Serbia - Piumatti, Giovanni; Lietz, Francesco; Marinkovic, Jelena; Bjegovic-Mikanovic, Vesna (Vojnosanitetski pregled, 2020)
Abstract Background/Aim. Self-rated health (SRH) is a widely adopted tool to compare health across countries. Relationships of socio-demographics with SRH in later life have been extensively cross-nationally observed. However, cross-comparisons of the effects of health behaviors (i.e., eating habits, smoking, and alcohol consumption) and health status (i.e., chronic diseases) on SRH are less frequent. Our aim was to examine SRH differences between older adults in Italy and Serbia and to observe the role of predictors of SRH particularly referring to health behaviors in both countries. Methods. Two samples of 4,406 Italians and 3,539 Serbs aged 65 and older were extracted from national health surveys conducted in 2013. For this secondary analysis, SRH, socio-demographics, health status variables, and health behavior factors were selected. In the multivariate logistic regression models, SRH was the dependent variable while the selected independent predictors were socio-demographics, characteristics related to health status and to health behavior. Results. Both Italians (30.3%) and Serbs (22.3%) reported lower values of good- or very good-SRH than the European average (36.9%). The logistic regressions showed that Serbs reported poor–SRH significantly more often than Italians. Moreover, gender, education level, chronic diseases, and daily life limitations resulted as significant predictors of SRH in both national samples. In addition, vegetables intake was positively associate to SRH among Italians, while among Serbs an adequate fruits intake was positively associated to SRH. Conclusion. Health behavior and health status factors are associated with better SRH in the population aged 65 and older. The effects differ between countries. It is essential that decision-makers of the implementation of international preventive strategies take into account the specific characteristics of countries in the organization of interventions for the aged population.